Effects of Different Rates of Poultry Manure and Split Applications of Urea Fertilizer on Soil Chemical Properties, Growth, and Yield of Maize - Aruna Olasekan Adekiya; Oluwaseyi Iyabo Ogunboye; Babatunde Sunday Ewulo; Adeniyi Olayanju (The Scientific World Journal)
During integrated nutrient management involving poultry manure (PM) and urea fertilizer (UF) for maize (Zea mays L.), it is necessary to investigate the best time to apply UF that will optimize soil chemical properties, growth, and yield of maize. Hence, studies were carried out to investigate the effect of different rates of PM and single and split applications (SA) of UF on soil chemical properties, growth, and yield of maize. The treatment involved three levels of PM (0.0, 4.0, and 8.0 t·ha−1) and four sets of periods of UF: (i) 0 kg N ha-1 (control), (ii) 120 kg N ha-1 applied at planting (AP), (iii) two SA of 120 kg N ha−1 (90 kg N ha-1 applied AP + 30 kg N ha-1 at thirty days after planting (DAP)), and (iv) three SA of 120 kg N ha-1 (60 kg N ha-1 applied AP + 30 kg N ha-1 thirty DAP + 30 kg N ha-1 at tasseling). The 12 treatments were arranged in a randomized complete block design and replicated three times. PM and UF alone and integrating UF with PM improved soil chemical properties, growth, and yield of maize compared with the control. SA of UF three times (60 + 30 + 30) had the most improved soil chemical properties, growth, and yield of maize. Results also showed that maize yielded higher under UF integrated with PM compared with their sole forms. Application of 60 + 30+30 with 8 t ha−1PM (60 + 30+30 + 8 t ha−1PM) or with 4 t ha−1PM treatments showed the highest growth and yield of maize, but due to the bulkiness, handling challenges, and cost of PM, 60 + 30+30 + 4 t ha−1PM is recommended. Therefore, for better growth and yield of maize, after the initial application of PM, UF application should be split-applied in accordance with plant growth and the pattern of uptake to avoid losses by leaching and therefore ensured that N level in the soil is high at the critical stage of N demand.